Doris Howes Calloway: Contributions to US Department of Agriculture Human Metabolic Research. Issue 5 (September 2022) - Kretsch, Molly J.; Yates, Allison A.; King, Janet C.; Butte, Nancy F.; Murphy, Suzanne P.; Blackburn, Mary L.
Abstract : When the US Department of Agriculture developed a new West Coast human nutrition research center in 1980, it turned to Dr Doris Calloway at the University of California at Berkeley, an internationally known and respected researcher in human nutrition, for expertise on controlled human nutrition metabolic research. This article highlights the importance and impact of Dr Calloway's leadership, expertise, and unique metabolic research methods in establishing human nutrition metabolic research at the US Department of Agriculture/Agricultural Research Service, Western Human Nutrition Research Center. It also provides a historical overview of the origins of the Western Human Nutrition Research Center and discusses the importance of a metabolic facility for human nutrition research.